The Law and Practice of the Ireland-Northern Ireland Protocol - McCrudden, Christopher (Social Sciences, 2022)
This edited collection provides expert commentary in each of the areas of legal practice that the complex Ireland-Northern Ireland Protocol affects. It provides comprehensive examination of the legal meaning and interpretation of the Protocol, offering insights from international law, European Union Law, domestic constitutional and public law.